Drogenspekulationen - Georg Dickmann (Recherches Germaniques)
Based on Laurent de Sutter’s theorem of ‘narco-capitalism’, the article examines the semantics and modes of subjectification of drugs and other precarious substances in Leif Randt’s novel Planet Magnon. Against the backdrop of how anesthetics work, the article shows that the sedating substances in Randt’s future fiction not only represent a decorative inventory of the fictional work, but also, as non-human agents, outline new modes of subjectification of the present, which the article tries to map with the concept of p‘sychopower’.